2004
DOI: 10.1590/s1516-14392004000100025
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Al-based thermal spray coatings for corrosion protection in high temperature refinery applications

Abstract: The application of thermal spray coatings has been effective in preventing corrosion of steel and iron products. It has been used in a wide range of applications spreading from the petroleum to the food industry. In this work, the performance and effectiveness of a two-layered aluminum-based thermal spray coating applied to an ASTM A387 G11 steel was evaluated. The coating structure was comprised of an inner Al-Fe-Cr layer and an outer layer of aluminum. Coated samples were tested in the reactor zone of a flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It has also been suggested that the amount of Sulphur and naphthenic acid in crude oil has an effect on the rate of corrosion. It has been the subject of extensive research in a number of studies, as shown in Figure (4) [35]. Predicting how naphthenic acid will corrode is hard because of the complex interactions between the type of crude oil, temperature, flow rate, type of alloy, surface state and Sulphur contented [36].…”
Section: Corrosion Caused By Naphthalenementioning
confidence: 99%
“…It has also been suggested that the amount of Sulphur and naphthenic acid in crude oil has an effect on the rate of corrosion. It has been the subject of extensive research in a number of studies, as shown in Figure (4) [35]. Predicting how naphthenic acid will corrode is hard because of the complex interactions between the type of crude oil, temperature, flow rate, type of alloy, surface state and Sulphur contented [36].…”
Section: Corrosion Caused By Naphthalenementioning
confidence: 99%
“…As was described in the previous test with NaCl solution, porosity gives to the ions in solution a free path through the coating, increasing the extent of the acid attack to the polymeric matrix. After some time, the stress in the coating increases and cracks are formed due to the corrosion process started 32 , causing the collapse of the coating, and consequently, weight loss.…”
Section: Corrosion Analysismentioning
confidence: 99%
“…Surface engineering, specifically through the advanced coating formation route, can be considered as an alternative strategy for high-temperature sulfidation and sulfidation-oxidation protection, especially if low-cost steels are used as substrate materials. Different coating materials and technologies for corrosion protection can be listed [ 21 , 22 , 23 , 24 , 25 , 26 ]. However, many coating options either have poor performance at high temperatures or insignificant thicknesses compared to possible structural defects, or poor adhesion and bonding to steel substrates, which leads to detachment issues at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%